LC–MS in the Development of Natural Product Based Antidiabetic Drugs: A Systematic Review - Kholilah Kholilah; Novi Yantih; Ridel Yosua Rumondor; Nur Pujiastuti (Faculty of Pharmacy Universitas Pancasila, 2026)
Natural products have great potential as a source for developing antidiabetic drugs, but matrix complexity and phytochemical variations are the main challenges in identifying bioactive compounds. This systematic literature review aims to evaluate the role of liquid chromatography–mass spectrometry (LC–MS) in the development of natural product-based antidiabetic drugs, particularly in type 2 diabetes mellitus (T2DM). The literature search was carried out following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines using the PubMed, Scopus, Web of Science, and ScienceDirect databases. The study results show that LC–MS plays an important role in comprehensive phytochemical profiling, high-confidence metabolite identification, and dereplication of complex natural matrices. Integration of LC–MS with metabolomics and pharmacology approaches provides a deeper mechanistic understanding of antidiabetic effects, including modulation of glucose and lipid metabolism. However, methodological heterogeneity between studies is still an obstacle, so protocol standardization and bioinformatics integration are needed to increase translational relevance towards clinical applications.